Tradition and innovation
1 online resource (xxi, 539 pages)
Keywords: The texts presented in Proportion Harmonies and Identities (PHI) Tradition and Innovation were compiled with the intent to establish a multidisciplinary platform for the presentation, interaction, and dissemination of researches. They also aim to foster the awareness and discussion on the topic of Tradition and Innovation, focusing on different visions relevant to Architecture, Arts and Humanities, Design and Social Sciences, and its importance and benefits for the sense of identity, both individual and communal. The idea of Tradition and Innovation has been a significant motor for development since the Western Early Modern Age. Its theoretical and practical foundations have become the working tools of scientists, philosophers, and artists, who seek strategies and policies to accelerate the development process in different contexts.